2017
DOI: 10.3892/etm.2017.5398
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β increases urinary corin in patients with primary proteinuric kidney diseases and in 293 cells

Abstract: Abstract. Corin is a serine protease that is important for the regulation of blood pressure and water balance. Corin was initially discovered in the heart, however, it has also been detected in kidney cells, though its function in the kidneys is unclear. To further investigate the function of corin in the kidney, the present study analyzed the levels of corin in urine and blood samples collected from normal individuals and patients with primary proteinuric diseases. The associations between the levels of corin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Corin has been reported to have anti-inflammatory role in natriuretic peptides treating Congestive heart failure ( 32 ). IL-1β and TNF-α could increase the level of urinary corin in patients with primary proteinuric kidney diseases ( 33 ). Recent studies have reported that corin participates in regulating several physiological signal transduction pathways, such as the MAPK, PI3K/Akt, and NF-κB pathways ( 4 , 5 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Corin has been reported to have anti-inflammatory role in natriuretic peptides treating Congestive heart failure ( 32 ). IL-1β and TNF-α could increase the level of urinary corin in patients with primary proteinuric kidney diseases ( 33 ). Recent studies have reported that corin participates in regulating several physiological signal transduction pathways, such as the MAPK, PI3K/Akt, and NF-κB pathways ( 4 , 5 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Renal Corin and both the mRNA and protein levels were found to be negatively related with chronic kidney disease, supporting that the decrease of renal Corin might be a novel biomarker of kidney injury. Another group reported that IL-1 β increases urinary Corin levels in primary proteinuric kidney diseases [7]. However, none of these studies separately analyzed the roles of renal and cardiac Corin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that Corin is also present in renal tissue [5], and the decrease in renal Corin is associated with chronic kidney disease [6]. Another group reported that proinflammation factors such as interleukin-1 β (IL-1 β ) and tumor necrosis factor- α (TNF- α ) upregulate Corin expression in patients with primary proteinuric kidney diseases [7]. However, the role of Corin in renal IR injury remains unclear.…”
Section: Introductionmentioning
confidence: 99%